Hubungan Self-Efficacy dengan Hasil Belajar Matematika Mahasiswa Prodi Tadris Matematika STAIN Gajah Putih Takengon - Hilliyani, Hilliyani; Wayuni, Septia (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2018)
Education is a very important thing in peoples lives. As is known that education will never be separated from learning activities, because without learning humans will not be able to do something. Science that a person can shape the attitudes, mindset, personality, views and insights that enlighten himself and others. It is realized that the importance of education for humans is a trigger in improving the quality of education. One effort to improve the quality of education is by giving birth to quality people. In the mathematics learning activities, it was found that most students were not confident about their abilities, and did not want to repeat the lesson again because they got bad grades. Based on the observations that the author did in Mathematics Education Department, self-efficacy (self-confidence) has not become a part that influences students mathematics learning outcomes. This study uses a correlation method with a quantitative approach. This study was conducted in the VII semester of the Mathematics Education Department STAIN Gajah Putih Takengon. The research sample was 21 students of Unit B Mathematics Education. Data collection tools are tests in the form of descriptions and questionnaires. Hypothesis testing using product moment test formula. Based on the results of research conducted on the students of the  Mathematics Education Department at STAIN GPA, then obtained the results of the hypothesis Ha is accepted that there is a relationship between self-efficacy and student mathematics learning outcomes in non-parametric statistical subjects of the seventh semester Mathematics Education STAIN GPA students. The results of this study are that there is a significant correlations between self-efficacy and mathematics mathematics learning outcomes of Mathematics Education Department students of STAIN GPA.